Monoclonal antibody with conformational specificity for a toxic conformer of amyloid β42 and its application toward the Alzheimer’s disease diagnosis - Murakami, Kazuma; Tokuda, Maki; Suzuki, Takashi; Irie, Yumi; Hanaki, Mizuho; Izuo, Naotaka; Monobe, Yoko; Akagi, Ken-ichi; Ishii, Ryotaro; Tatebe, Harutsugu; Tokuda, Takahiko; Maeda, Masahiro; et al. (Scientific reports, 2016)
Amyloid β-protein (Aβ42) oligomerization is an early event in Alzheimer’s disease (AD). Current diagnostic methods using sequence-specific antibodies against less toxic fibrillar and monomeric Aβ42 run the risk of overdiagnosis. Hence, conformation-specific antibodies against neurotoxic Aβ42 oligomers have garnered much attention for developing more accurate diagnostics. Antibody 24B3, highly specific for the toxic Aβ42 conformer that has a turn at Glu22 and Asp23, recognizes a putative Aβ42 dimer, which forms stable and neurotoxic oligomers more potently than the monomer. 24B3 significantly rescues Aβ42-induced neurotoxicity, whereas sequence-specific antibodies such as 4G8 and 82E1, which recognizes the N-terminus, do not. The ratio of toxic to total Aβ42 in the cerebrospinal fluid of AD patients is significantly higher than in control subjects as measured by sandwich ELISA using antibodies 24B3 and 82E1. Thus, 24B3 may be useful for AD diagnosis and therapy.